Coxiella effector protein CvpF subverts RAB26-dependent autophagy to promote vacuole biogenesis and virulence. Issue 3 (4th March 2021) - Siadous, Fernande Ayenoue; Cantet, Franck; Van Schaik, Erin; Burette, Mélanie; Allombert, Julie; Lakhani, Anissa; Bonaventure, Boris; Goujon, Caroline; Samuel, James; Bonazzi, Matteo; Martinez, Eric
ABSTRACT: Coxiella burnetii, the etiological agent of the zoonosis Q fever, replicates inside host cells within a large vacuole displaying autolysosomal characteristics. The development of this compartment is mediated by bacterial effectors, which interfere with a number of host membrane trafficking pathways. By screening a Coxiella transposon mutant library, we observed that transposon insertions in cbu0626 led to intracellular replication and vacuole biogenesis defects. Here, we demonstrate that CBU0626 is a novel member of the Coxiella vacuolar protein (Cvp) family of effector proteins, which is translocated by the Dot/Icm secretion system and localizes to vesicles with autolysosomal features as well as Coxiella -containing vacuoles (CCVs). We thus renamed this effector CvpF for Coxiella vacuolar protein F. CvpF specifically interacts with the host small GTPase RAB26, leading to the recruitment of the autophagosomal marker MAP1LC3B/LC3B (microtubule associated protein 1 light chain 3 beta) to CCVs. Importantly, cvpF ::Tn mutants were highly attenuated compared to wild-type bacteria in the SCID mouse model of infection, highlighting the importance of CvpF for Coxiella virulence. These results suggest that CvpF manipulates endosomal trafficking and macroautophagy/autophagy induction for optimal C. burnetii vacuole biogenesis. Abbreviations: ACCM: acidified citrate cystein medium; AP: adaptor related protein complex; CCV: Coxiella -containing vacuole; Cvp: Coxiella vacuolar protein; GDI: guanosine nucleotide dissociation inhibitor; GDF: GDI dissociation factor; GEF: guanine exchange factor; LAMP1: lysosomal associated membrane protein 1; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MTORC1: mechanistic target of rapamycin kinase MTOR complex 1; PBS: phosphate-buffered saline; PMA: phorbol myristate acetate; SQSTM1/p62: sequestosome 1; WT: wild-type.